Genotype-specific modulation of drought tolerance by arbuscular mycorrhizal symbiosis in foxtail millet - Chang, O-Chi; Lin, Wei-Yi (Frontiers in Plant Science, 2025)
Drought stress is a major environmental factor limiting crop productivity. Arbuscular mycorrhizal fungi (AMF), as beneficial soil microbes, can improve plant growth and stress resilience; however, the effectiveness of this symbiosis is often influenced by the host plant’s genetic background. In this study, we investigated the interaction between AM symbiosis and drought tolerance in two foxtail millet (Setaria italica) accessions with contrasting drought responses: the drought-tolerant ISE42 and the drought-sensitive TT8. Following a 14-day drought treatment, both accessions exhibited wilting, but AMF-colonized plants reduced malondialdehyde accumulation, indicating alleviated oxidative stress. Notably, only colonized ISE42 plants recovered upon rewatering. Although AMF colonization was confirmed by staining and qRT-PCR, AM symbiosis-conserved genes were strongly induced in ISE42 and TT8 only at 7 days post-treatment. Transcriptomic analysis further revealed that AM symbiosis significantly enhanced the expression of genes involved in nitrogen transport, assimilation, lignin metabolism, and cellulose biosynthesis in ISE42, suggesting improved nutrient uptake and cell wall reinforcement as key mechanisms underlying enhanced drought tolerance. In addition, drought-induced stress hormone signaling pathways were downregulated in colonized ISE42 roots, pointing to AM symbiosis-mediated stress alleviation. Together, these results demonstrate genotype-specific effects of AMF on drought tolerance and recovery capability, and highlight the importance of considering host genetic variation in the application of AMF for crop improvement.